Cleptoherbário : uma estratégia para o ensino de Botânica - Porto, Andréia Aparecida Batista (2022)
Many teachers remain constancy with the single teaching method (expository class). Students generally struggle to assimilate the contents, as they claim that the terms used are complicated to write and pronounce. This work is quantitative-qualitative research that aimed to create, apply, evaluate, and disseminate a sequence of investigative teaching that can be used by other teachers in Botany classes on angiosperm morphologies, with emphasis on the types of roots, stems, and leaves. The proposal was applied remotely to 23 students from the 2nd year of high school at a state public school located in the municipality of Campo Verde-MT between May and June 2021. The SEI presented in this work is organized into six stages: problematization, experimentation, theoretical basis, description, exsiccates, and kleptoherbarium. Kleptoherbarium is an informal term that was used to refer to a type of portable herbarium, and it was configured as a teaching and evaluation tool. Since the evaluation must accompany the teaching and learning process, then active methodologies require active evaluation, so the form of evaluation was consistent with the methodologies used. Students received a printed guide, an experimentation kit, and a biology book to participate in this research. Data were collected through the guides that were returned to the school, as well as information posted in the WhatsApp group and synchronous communication in Google Classroom. One of the stages that the students found most difficult was precisely the one they liked the most, which is the experimentation stage. The results indicate that this SEI has good applicability and allows the application of investigative teaching in Botany classes, thus making the teaching and learning process much more dynamic and attractive for students and teachers.